The Judicial Reasoning Behind Decision No. 262/Pid.B/2018/Pn.Skt on a Case of Mass Violence: The Perspective of Human Aggressiveness and the Ashobiyah Terminology - Purwadi Wahyu Anggoro; Khudzaifah Dimyati; Absori; Kelik Wardiono; Sri Waljinah (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of the study: This research aimed to analyze the judicial rationing behind Decision No. 262/Pid.B/2018/Pn.Skt. According to Article 170 of the Indonesian Criminal Code in the legal event of a mass violence crime that occurred in Surakarta City.  Methodology: This was normative legal research that used the case approach. It emphasized the legal consideration of judges in deciding and giving a verdict upon a case. Results: This research analyzed Decision No. 262/Pid.B/2018/Pn.Skt. Judges considered that the actions committed by the group of perpetrators originated from the aggressive nature of humans due to their animal power that can cause law-violating actions. This aggressive human nature in a group caused a sense of affection and bond creates similarities in desires, goals, and ideas. It resulted in a sense of solidarity in the group according to the ashobiyah terminology. Applications of this study: to provide knowledge on: (1) the judicial analysis based on the factors that influence the occurrence of mass violence; and (2) the judicial consideration in deciding upon a case of mass violence in Surakarta City based on the judicial rationing in Decision No. 262/Pid.B/2018/PN.Skt. Novelty/Originality of this study: This paper provided new information on the action of mass violence on Decision No. 262/Pid.B/2018/PN.Skt correlated with Ibnu Khaldun’s ashobiyah terminology. Keywords: judicial reasoning, mass violence, aggressivity, ashobiyah    ABSTRAK  Tujuan: Penelitian ini bertujuan untuk menganalisis pertimbangan yuridis di balik Putusan Nomor 262/Pid.B/2018/Pn.Skt. Menurut Pasal 170 KUHP dalam peristiwa hukum tersebut, tindak pidana kekerasan massal terjadi di Kota Surakarta.  Metodologi: Penelitian ini merupakan penelitian hukum normatif yang menggunakan pendekatan kasus. Ditekankan pada pertimbangan hukum hakim dalam memutus dan memberikan putusan atas suatu perkara.  Hasil: Penelitian ini menganalisis Keputusan No. 262/Pid.B/2018/Pn.Skt. Hakim menilai bahwa perbuatan yang dilakukan oleh kelompok pelaku tersebut berawal dari sifat agresif manusia karena animal power yang dapat menimbulkan perbuatan melanggar hukum. Sifat agresif manusia dalam suatu kelompok menimbulkan rasa kasih sayang dan ikatan yang menimbulkan kesamaan keinginan, tujuan, dan gagasan. Hal itu mengakibatkan rasa solidaritas dalam kelompok menurut terminologi ashobiyah.  Aplikasi penelitian ini: memberikan pengetahuan tentang (1)analisis yuridis berdasarkan faktor-faktor yang mempengaruhi terjadinya kekerasan massal, (2)pertimbangan yuridis dalam memutus perkara kekerasan massal di Kota Surakarta berdasarkan yuridis rationing dalam Putusan No. 262/Pid.B/2018/PN.Skt.  Kebaruan/Orisinalitas: Tulisan ini memberikan informasi baru tentang aksi kekerasan massal pada Putusan No. 262/Pid.B/2018/PN.Skt yang berkorelasi dengan terminologi ashobiyah Ibnu Khaldun.  Kata kunci: penalaran yudisial, kekerasan massal, agresivitas, ashobiyah